2017
DOI: 10.3389/fmicb.2017.01316
|View full text |Cite
|
Sign up to set email alerts
|

Captivity Shapes the Gut Microbiota of Andean Bears: Insights into Health Surveillance

Abstract: The Andean bear is an endemic species of the tropical Andes who has an almost exclusively plant-based diet. Since herbivorous mammals do not carry enzymes for fiber degradation, the establishment of symbiosis with cellulolytic microorganisms in their gastrointestinal (GI) tract is necessary to help them fulfill their nutritional needs. Furthermore, as described for other mammals, a stable, diverse, and balanced gut microbial composition is an indicator of a healthy status of the host; under disturbances this b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 56 publications
(96 reference statements)
5
60
0
Order By: Relevance
“…Bray-Curtis distances showed that wild-captured samples clustered on their own while colony and colony-transitional samples clustered together ( Figure 4 a). This is in line with previous studies that show different microbial diversity and community structure in captive vs wild conspecifics [ 28 , 48 , 68 , 69 ]. PLS-DA analysis also indicated separation of wild-captured samples ( Figure 2 a).…”
Section: Discussionsupporting
confidence: 93%
“…Bray-Curtis distances showed that wild-captured samples clustered on their own while colony and colony-transitional samples clustered together ( Figure 4 a). This is in line with previous studies that show different microbial diversity and community structure in captive vs wild conspecifics [ 28 , 48 , 68 , 69 ]. PLS-DA analysis also indicated separation of wild-captured samples ( Figure 2 a).…”
Section: Discussionsupporting
confidence: 93%
“…The current evidence confirms that captivity alters the community structure, and in many cases, the diversity of animal gut microbiota (e.g. Borbon‐Garcia, Reyes, Vives‐Florez, & Caballero, ; Cheng et al, ; Delport, Power, Harcourt, Webster, & Tetu, ; McKenzie et al, ; Wasimuddin et al, ), although there is little evidence to date equating these changes with harm.…”
Section: Introductionsupporting
confidence: 70%
“…(e.g Borbon-Garcia, Reyes, Vives-Florez, & Caballero, 2017;Cheng et al, 2015;Delport, Power, Harcourt, Webster, & Tetu, 2016;McKenzie et al, 2017;Wasimuddin et al, 2017),. although there is little evidence to date equating these changes with harm.…”
mentioning
confidence: 99%
“…Our results may not be representative of the entire proboscis monkey population due to the small sample size (N = 6) with high individual variation within the same environmental condition. Effects of diet on both foregut and hindgut microbial patterns have previously been shown in various free-ranging and captive animals (Dill-McFarland et al, 2016;Borbon-Garcia et al, 2017;Hale et al, 2018), although these results are rarely shown together with information on the living environment of the animals. The geographic region Sundaland, which includes our study sites, is a large reservoir of endemic tropical plant and animal species such as the proboscis monkey (Myers et al, 2000).…”
Section: Resultsmentioning
confidence: 99%